The effect of IFRS Implementation Level and Audit Quality on Timely Loss Recognition in Companies Listed on Indonesia Stock Exchange - Dana Puspita Rahmawati; Lulus Kurniasih (Journal of Economics, Business, and Accountancy Ventura, 2017)
This study aims to examine the effect of IFRS implementation and audit quality as represented by public accountant firms’ size on timely loss recognition in Indonesia. This study uses firm size, profitability, and growth as control variables. This research was conducted in the non state-owned companies and non financial companies listed on Indonesia Stock Exchange in 2012-2015. This study used a purposive sampling method for getting the sample. Multiple regression analysis was used as the main analysis and the results show that timely loss recognition is affected by audit quality and firm size. However, this study finds that IFRS implementation, profitability, and growth don’t have significant effect on timely loss recognition.